IMPACT ASSESSMENT OF FUEL SUBISDY REMOVAL POLICY IN SMALL RUMINANTS PRODUCTION IN ABEOKUTA AREA OF OGUN STATE - Ogungbesan, A.M.; Bankole, T.O.; Fasina, O.E.; Ogunaike, M.G.; Ologbon, A.O.C.; Dada. O.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study evaluated the impact assessment of fuel subsidy removal policy in small ruminant’s production in Abeokuta area of Ogun State. Purposive sampling technique was used in selecting 60 respondents and data were collected using structured questionnaire. The results revealed that majority of the small ruminant farmers (60.0%) aged between 31-40 years had secondary education, 65% of the farmers had household size of 0-5, while the butcher had experience of 5- 25 years (46.7%) and their source of income is from personal savings (68.3%). Similarly, majority of the small ruminant farmers (93.3%) and (95.3%) encountered challenges of high cost of feed and price fluctuation respectively. Most of the respondents didn’t have challenges of low patronage from customer (58.3%). Key challenges faced by respondents in the study area were high mortality rate (70.0%), high cost of medications and drugs (86.7%), high cost of veterinaries services (86.7%), scarcity of feed (83.3%), high cost in purchasing small ruminant animals (96.7%) and experiences difficulty in procuring loan and credit (68.3%). In addition, there is significantly (P<0.05) difference during and after subsidy era on cost and return estimate of small ruminant production. Majority (88.3% ) of the respondents employed the use of local agro by products, industrial waste as feed (65.0%), uses traditional medications (66.7%) uses family as labor (58.3%) as coping strategies to mitigate the constraints of fuel subsidy removal. It is therefore concluded that there is significant effect of the removal of fuel subsidy on small ruminant farmers in the study area.